Production of newcastle disease virus by vero cells grown on cytodex 1 microcarriers in a 2-litre stirred tank bioreactor - Arifin, Mohd Azmir; Mel, Maizirwan; Abdul Karim, Mohamed Ismail; Ideris, Aini (Hindawi Publishing Corporation, 2010)
The aim of this study is to prepare a model for the production of Newcastle disease virus (NDV) lentogenic F strain using cell culture in bioreactor for live attenuated vaccine preparation. In this study, firstly we investigated the growth of Vero cells in several culture media. The maximum cell number was yielded by culture of Vero cells in Dulbecco’s Modified Eagle Medium (DMEM) which was 1.93 × 106 cells/ml. Secondly Vero cells were grown in two-litre stirred tank bioreactor by using several commercial microcarriers. We achieved the maximum cell concentration about 7.95 × 105 cells/ml when using Cytodex 1. Later we produced Newcastle Disease virus in stirred tank bioreactor based on the design developed using Taguchi L4 method. Results reveal that higher multiplicity of infection (MOI) and size of cell inoculums can yield higher virus titer. Finally, virus samples were purified using high-speed centrifugation based on 3∗∗(3-1) Fractional Factorial Design. Statistical analysis showed that themaximum virus titer can be achieved at virus sample concentration of 58.45% (v/v), centrifugation speed of 13729 rpm, and centrifugation time of 4 hours. As a conclusion, high yield of virus titer could be achieved through optimization of cell culture in bioreactor and separation by high-speed centrifugation.